Exploring Arabic Diglossia in Learning Kalām: Bridging the Gap in Daily Communication - Annindita Hartono Putri; Anisatu Thoyyibah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study explores the phenomenon of Arabic diglossia specifically the coexistence and functional differentiation between fusha (formal) and ‘amiyah (informal) varieties in the instruction of speaking skills (kalām) at Markaz Arabiyah Pare, an Arabic learning center in Kediri, East Java, Indonesia. Centering on the Akbarnas (Akselerasi Bahasa Arab Nasional, National Arabic Language Acceleration) class program, the research seeks to identify the types, contexts, and underlying factors influencing diglossic language use in daily communicative practices. Situated within the broader discourse of sociolinguistics and Arabic language pedagogy, this study addresses a notable gap in empirical research concerning the implementation of diglossia within non-formal educational settings. Employing a qualitative descriptive approach, data were collected through observation, semi-structured interviews, and ethnographic documentation, and analyzed using the Miles and Huberman model. The findings demonstrate that fusha predominates in formal classroom instruction, while ‘amiyah is more commonly employed in informal, non-academic interactions thus enhancing students’ communicative adaptability. This dual usage reflects the institution’s language policy. It is also shaped by instructors’ backgrounds many studied in the Middle East and students’ prior exposure to Arabic-speaking contexts. The study concludes that integrating both varieties into instructional design fosters pragmatic competence and contextual fluency. These findings offer significant implications for Arabic language educators and curriculum developers seeking to bridge the divide between formal instruction and real-world language use.